FAKTOR YANG MEMPENGARUHI PEMILIHAN METODE KONTRASEPSI MANTAP PRIA DI KECAMATAN KAPAS KABUPATEN BOJONEGORO TAHUN 2014 - Eka Rahayu Puji L, Eka Rahayu Puji L (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2014)
This research has purpose to analize factor that influence choosing man steady contraception method. The factors which is research and guessed influence choosing man steady contraception methode are knowledge, available budget and man domination in taking decission.Theys research with is observation with research design cross sectional study that is that is data collection of dependent and independent variable in the some time. The population in this research is fertile age marriage man who join contraception in Kapas District, Bojonegoro Regency in 2008 amount 50 people. The research sample is man participant contraception method that fulfiil inclusion criteria that is man who doesn?t  have health problem for man reproduction, willin to join research, wife?s age >25 years old, has child > 2, the Indonesian nation. While the man exculision criteria is man who has history reproduction health problems, man with no reproduction  health problem but doesn?t willing to joint research. Analisys data technic to test factor which has influence toward choosing man steady contraception method is descriptive and analitic. Descriptive analisys to get description independent variable and dependent variable by using frequency distribution table. Before doing double logistic regretion test cach independent is done simple logistic regresion tes with alpha < 0,25 to know which variable as candidate variable. The result of simple logistic regresion analisys p < 0,25 is entered as multiple logistic regression candidate. The result of research with simple logistic regression test shows that variable influence choosing man steady contraception method so the testing just use simple logistic regresion test.The result of this research shows that there is available budget influence choosing man steady contraception method.  Keyword : contraception method, vasectomy, factors, influence